G593 Longitudinal health and social outcomes following adolescent sexual assault: a prospective cohort study. (May 2019) - Khadr, SN; Clarke, V; Wellings, K; Goddard, A; Kramer, T; Viner, R
Abstract : Aims: To describe medium-term health and social outcomes in young people 13–15 months post-sexual assault. Method: Longitudinal mixed methods study examining the trajectories of adolescents presenting to the Sexual Assault Referral Centres (SARCs) serving a large, diverse city soon after assault. Data were collected within 6 weeks (T0), 4–5 months (T1) and 13–15 months (T2) of assault regarding young people's health, education status and service use. Results: 141 (29%) of 491 eligible young people were recruited (95% female, mean age [SD] 15.6 [1.3] years). 106 (75%) were reviewed at T1 and 75 (53%) at T2, when 19 took part in a semi-structured interview. 92% of participants had been raped. Nearly half were non-white; two-thirds from low-income backgrounds and half lived with only one parent. Participants had high levels of special educational needs; half had accessed mental health support in the 12 months prior to assault; half had been involved with social services and 20% had been in care. One in 3 had experienced a previous sexual assault. Mental health symptom levels were exceedingly high at T0. Despite many accessing support services, 54%, 59% and 72% of participants remained at risk for depression, anxiety disorder and post-traumatic stress disorder 13–15 months post-assault. Persistent (>30 days) absence from school doubled between T0 and T2 from 22% to 47% and was associated with baseline psychosocial risk factors. Qualitative data suggested a bi-directional relationship between mental health problems and disengagement from school, as well as poor understanding on the part of schools how to support young people post-assault. Baseline levels of smoking, alcohol use and drug use were high and increased during the study period but with no significant change by T2. Conclusion: Adolescents who presented after sexual assault had high levels of deprivation and pre-existing vulnerability. Many remained at risk for disorders 13–15 months post-assault, highlighting the need for specialist intervention and ongoing support. A key area of concern for young people was disruption to their education. Multidisciplinary interventions are needed to prevent social exclusion and further widening of health inequalities in this population, and to support young people in their recovery and to lead full lives.